Simultaneous Measurement of Shape and Temperature in the Substrate-Attaching-Fibers Sensing System - Shiyuan Zhao; Jiwen Cui; Chaoqiang Yang; Zhenyang Ding; Jiubin Tan (IEEE Photonics Journal, 2017)
We design a dual-parameter sensor which can simultaneously measure the shape and temperature in the substrate-attaching-fibers sensing system. Two kinds of fibers with different diameter are attached on a shape memory alloy wire substrate with an angle of 90°. The measurement principle is demonstrated in details. Meantime, the fabrication and calibration process are illustrated. A sensor with a length of 150 mm is final made. The maximum measurement errors are 12 mm in position and 0.45  °C in temperature.